Toward a monophyletic Paragympteris (Cheilanthoideae, Pteridaceae): description of Sericopteris gen. nov. - Zhao, Jing; Liang, Zhen-Long; Yu, Hong; He, Zhao-Rong; Zhou, Xin-Mao (Phytotaxa, 2025)
Recent phylogenetic studies based on plastid, mitochondrial, and nuclear data supported that Paragymnopteris s.l. was paraphyletic and contained two fully supported clades. We here review the circumscription of Paragymnopteris s.l. and find that one of the clades has densely sericeous hairs on the abaxial surface and is described as the new genus Sericopteris Jing Zhao, X.M. Zhou & Z.R. He.